Menstrual hygiene management in Mpolonjeni, Swaziland : experiences and practices of girls in a rural school - Khaweka, Sakhile Melody (My University, 2017)
Developments in information and communication technologies (ICTs) have revolutionised banking, in that consumers can make use of mobile devices to conduct daily banking, independent of a traditional bank branch. The adoption of mobile banking has continued to be low in South Africa, at 24%, while the mobile phone market has experienced a significant increase in market penetration to 96%. However, very few studies have investigated the impact of mobile banking among bottom of the pyramid consumers. Therefore, the purpose of this study is to investigate the influence of financial literacy, social pressure and perceived credibility on the adoption of mobile banking among the bottom of the pyramid consumers in South Africa. An empirical study on bottom of the pyramid consumers in Johannesburg, South Africa with a sample of 235 questionnaires was conducted. The measurement items were assessed through three hypotheses using Structural Equation Modelling with IBM SPSS 23 and AMOS 23. The results confirm that all three hypotheses are significant and supported by indicating that financial literacy, social pressure and perceived credibility have an impact on mobile banking among bottom of the pyramid consumers. The findings revealed that social pressure and mobile banking was the weakest significant relationship, while perceived credibility had the strongest significant relationship on mobile banking. This study adds to the theoretical knowledge of financial literacy, social pressure and credibility as the factors that impact on mobile banking among bottom of the pyramid consumers. The managerial implications of the study indicate that in order for managers to increase mobile banking adoption, they need to create strategies that will drive education around mobile banking, use other people as advocates and place emphasis on communicating the safety and privacy of the services. Recommendations, limitations and future research on mobile banking are discussed. Keywords: Mobile Banking, Financial Literacy, Perceived Credibility, Social Pressure, Bottom of the Pyramid
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits School of Governance, 2017
Keywords: Teenage girls--Education--Swaziland; Teenage girls--Health and hygiene--Swaziland; Menstruation--Social aspects--Swaziland; Rural schools--Swaziland--Management